A Study Of Canine Dirofilariasis In Kuala Lumpur - Dhaliwal, Gurmeet Kaur (1988)
Although much importance has been placed on human filariasis , work on canine filariasis is limited in this country . This study was carried out to obtain a general overview on the status of canine dirofilariasis in Kuala Lumpur. Throughout a one year study , parasitological records